Pengembangan Media Edukasi Digital : Website Promosi Kesehatan sebagai Strategi Pencegahan Stunting pada Pengguna (Siswa) di Kabupaten Sumbawa - Rahmania Ambarika; Indasah Indasah; Has’ad Rahman Attamimi (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Stunting remains a major public health concern in Indonesia, including in Sumbawa Regency. Preventive efforts must be carried out upstream, one of which is through nutrition and health education for adolescents as future parents. This community service activity aimed to develop a digital-based educational media in the form of the RAMPES (Remaja Peduli Stunting/Adolescents Care for Stunting) website as an interactive learning tool to improve adolescents’ literacy in nutrition and health. The method applied combined participatory, educational, and co-creation approaches, including problem identification, digital content development, online and offline dissemination, and evaluation through pre- and post-tests. The product developed was a website containing digital modules, educational videos, presentation materials, and interactive exercises designed to match adolescent characteristics. The website was disseminated online via Zoom with the participation of 233 students from 47 senior high schools/vocational schools (SMA/SMK), and offline at five pilot schools: SMA Negeri 1 Sumbawa, SMA Negeri 2 Sumbawa, SMA Negeri 3 Sumbawa, SMK Negeri 1 Sumbawa, and SMK Islam Farmasi Sumbawa. Evaluation results indicated an improvement in knowledge, with the “poor” category decreasing from 21.6% to 16.2% and the “fair” category increasing from 40.5% to 45.9%. A more significant improvement was observed in attitudes, with the “good” category rising from 23.4% to 63.1% and the “poor” category decreasing sharply from 25.2% to 3.6%. These findings demonstrate that website-based education is effective in enhancing adolescent nutrition literacy and fostering positive attitudes toward stunting prevention. This initiative also supports the Bakti Stunting Program implemented by KCD DIKBUD Sumbawa and serves as a strategic innovation in the digital transformation of education and health sectors.